The Role of Role Play Method in Grade 8 Students’ Mastery of Maharat Kalam - Asyifa Azzaroh; Mohammad Nu'man (JURNAL IJ-ATL, 2025)
Arabic speaking skills (maharah al-kalam) are crucial for effective communication and learning in Islamic education. This study aimed to examine how the role-play method influences Grade 8 students’ mastery of maharah al-kalam. A qualitative case study was conducted involving five students and two Arabic teachers, with data collected through interviews, classroom observations, and documentation. The findings revealed that role play significantly increased students’ speaking confidence, promoted active participation, and expanded vocabulary during interactive sessions. The study contributes to the understanding of effective, student-centered learning strategies in Islamic education, particularly in contexts combining traditional values with modern pedagogical approaches. Practically, the results suggest that implementing structured role play activities can enhance oral proficiency, engagement, and communication skills, providing teachers with actionable strategies to foster more interactive and meaningful Arabic learning experiences.